Adaptation of Religious/Spiritually Integrated Practice Assessment Scale-Client Attitude (RSIPAS-CA) in Indonesia - Fadhilla Najmi Qinthara; Yuliana Hanami (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Assessment tools are important to helps Indonesian practitioners to understand the preference of clients toward integration of religious/spiritual values in mental health services. Therefore, this study aimed is to adapt the Religious/Spiritually Integrated Practice Assessment Scale - Client Attitude (RSIPAS-CA) by Oxhandler et al. (2018) to Indonesian context as well as describing the responses of participants. Adaptation of this scale was conducted quantitatively, and the process included translations and expert reviews, followed by data collection on 77 participants who had or are currently receiving mental health services. The results showed that the Indonesian version of the RSIPAS-CA with 9 items, had good discriminating power, content validity, reliability, and construct validity. Most participants had a positive view towards the integration of religion/spirituality in the context of mental health services. This questioneer facilitated practitioners to conduct assessments and served as a measuring tool in future studies.